Antioxidant Activity Assessment and Profiling of Total Phenolic and Flavonoid Contents in Bay Leaf Extract (Syzygium polyanthum Folium) - Hutagaol, Cindy Jesika; Yunus, Muhammad; Piska, Finna (CV. Nusantara Scientific Medical, 2026)
Bay leaf (Syzygium polyanthum (Wight) Walp.) is a traditional medicinal plant containing phenolic and flavonoid compounds with potential antioxidant properties. Free radicals contribute to various degenerative diseases, highlighting the need for safe and effective natural antioxidants. This study aimed to evaluate the antioxidant activity of ethanolic extract of bay leaves using the DPPH method and to determine its total phenolic and flavonoid contents. This experimental laboratory study employed maceration extraction using 96% ethanol. Antioxidant activity was assessed by the DPPH radical scavenging assay at 517 nm and expressed as IC₅₀ value. Total phenolic content was determined using the Folin–Ciocalteu method at 765 nm and expressed as mg gallic acid equivalents (GAE)/g extract, while total flavonoid content was measured using the AlCl₃ colorimetric method at 430 nm and expressed as mg quercetin equivalents (QE)/g extract. The results showed that the ethanolic extract exhibited a strong antioxidant activity with an IC₅₀ value of 33.43 ppm. The total flavonoid content was 14.4992 mg QE/g extract (1.4499%) with excellent linearity (r² = 0.99747), while the phenolic calibration curve showed good linearity (r² = 0.99045). In conclusion, the ethanolic extract of S. polyanthum leaves demonstrates strong antioxidant activity supported by its phenolic and flavonoid contents, indicating its potential as a natural antioxidant source.